Respuesta :

Answer:

x

Step-by-step explanation:

If you multiply a function and its inverse, you will will always get x back.

f-1( f(x) ) = x

Answer:

the value of G^-1(G(x)) is x

Step-by-step explanation:

We define G^-1(x) as the inverse of G(x), when we talk about functions inverse does not work like with the numbers, this means that G^-1(x) is not equal to 1/G(x).

Inverse means that if:

G(x) = y

then:

G^-1(y) = x

then if we have:

G^-1(G(x)) = G^-1(y) = x

so when we evaluate a given function in its inverse, the result is the input of the function.

And is the same in the case:

G(G^-1(x)) = x